Avaliação da metilação e do polimorfismo no gene IL-6 e sua expressão na periodontite - Florenca Abdanur Stefani (2010)
Periodontitis is considered an inflammatory disorder of bacterial etiology that results in periodontal tissue destruction, as a result of complex interactions between periodontal pathogens and host and immune responses. Genetic and epigenetic mechanisms may modulate the individual response since it is able to able to influence the gene expression of important inflammatory mediators. The aim of this study was to evaluate the methylation pattern, gene polymorphism and expression of the Interleukin-6 (IL-6) in gingival samples from individuals with chronic periodontitis. Gingival biopsies were collected from 21 patients with chronic periodontitis and 21 patients with clinically healthy periodontium. Histologic sections stained by hematoxylin-eosin were used for histopatological evaluation. Methylation-specific polymerase chain reaction was used to verify the DNA methylation pattern and the polymorphism IL-6 -174 C/G was studied by polymerase chain reaction (PCR) amplification and restriction endonuclease digestion (HspII). The IL-6 gene expression was assessed by quantitative real-time PCR. The number of inflammatory cells in tissue fragments with chronic periodontitis was higher than in the control group (p = 0.0001) and the inflammatory infiltrate was predominantly mononuclear. The methylation pattern in two different regions of the gene IL-6 was not statistically different between the groups, the most of samples had were partially methylated. In polymorphism assay, no statistical difference in the distribution of genotypes GG, GC and CC, and allele G and C for the IL-6 gene in both groups were observed. The expression of IL-6 was higher in the group with periodontitis (p = 0.041). The high expression of IL-6 is an important factor related to chronic periodontitis, but was not associated with methylation status or the -174 (G/C) genetic polymorphism, suggesting that other mechanisms are involved in this gene transcription regulation.